Optimising the expansion of the national bowel cancer screening program - influencing the national policy agenda - Cenin, Dayna; St John, J.; Ledger, M.; Slevin, T.; Lansdorp-Vogelaar, I. (WILEY-BLACKWELL, 2014)
Background and Context: The National Bowel Cancer Screening Program (NBCSP) has experienced a long and drawn-out expansion. Commenced in 2006, it invited just two age groups, those turning 55 and 65 years. Through the years, various commitments and extensions have been made. Finally, in the 2012–13 Budget, the Federal Government made an on-going commitment and agreed to fully implement biennial screening for 50–74 year-olds. While this commitment was welcomed, concerns were raised over the lengthy implementation time-line (2034) which could have serious implications on bowel cancer Aim: To estimate the impact and compare various expansion scenarios of the (NBSCP) in terms of bowel cancer deaths prevented due to early identification and prevention of bowel cancer. Strategy/Tactics: Using a well-established, validated computer simulation model for bowel cancer screening (MISCAN-Colon), adjusted to reflect the Australian situation, five implementation scenarios were developed and modelled. Their impact on bowel cancer mortality was compared. This is the first time Australian data has been used in internationally recognised cancer modelling software, allowing researchers to quantify the number of deaths prevented as a result of various screening scenarios for bowel cancer and enabling a comparison between the current adhoc screening program and the various simulated scenarios.Programme/Policy Process: The preliminary results of the modelling were made available for the Cancer Council Australia's election manifesto in July 2013. During the 2013 election campaign, the Shadow Health Minister, using information provided in the manifesto, announced that under a coalition government the NBCSP would be fully implemented by 2020. This commitment is expected to be translated into policy in the near future. Outcomes/What was Learned: Our results provided a strong argument to act with immediacy. The importance of relevant and timely evidence-based research to advocate for changes to public policy cannot be underestimated.